Tsunami Science and Engineering II - Heller, Valentin (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Earthquake-tsunamis, including the 2004 Indian Ocean Tsunami and the 2011 T?hoku Tsunami in Japan, serve as tragic reminders that such waves pose a major natural hazard. Landslide-tsunamis, including the 1958 Lituya Bay case, may exceed 150 m in height, and similar waves generated in lakes and reservoirs may overtop dams and cause significant devastation. This book includes nine peer-review articles from some of the leading experts in the field of tsunami research. The collection represents a wide range of topics covering (i) wave generation, (ii) wave propagation, and (iii) their effects. Within (i), a tsunami source combining an underwater fault rupture and a landslide are addressed in the laboratory. Within (ii), frequency dispersion with the nonlinear shallow-water equations is considered and a detailed account of the 1755 Lisbon earthquake, tsunami, and fire in downtown Lisbon is presented. Two articles involve all three phases (i) to (iii), including runup and dam over-topping. Within (iii), a new semi-empirical equation for runup is introduced and the interaction of tsunamis with bridges and pipelines is investigated in large laboratory experiments. This state-of-the-art collection of articles is expected to improve modelling and mitigate the destructive effects of tsunamis and inspire many future research activities in this challenging and exciting research field.